2006
DOI: 10.1093/jxb/erj083
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the three Arabidopsis thaliana RAD21 cohesins reveals differential responses to ionizing radiation

Abstract: The RAD21/REC8 gene family has been implicated in sister chromatid cohesion and DNA repair in several organisms. Unlike most eukaryotes, Arabidopsis thaliana has three RAD21 gene homologues, and their cloning and characterization are reported here. All three genes, AtRAD21.1, AtRAD21.2, and AtRAD21.3, are expressed in tissues rich in cells undergoing cell division, and AtRAD21.3 shows the highest relative level of expression. An increase in steady-state levels of AtRAD21.1 transcript was also observed, specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 75 publications
(138 reference statements)
1
65
0
Order By: Relevance
“…Constitutive expression of cohesin subunits using 35S promoter was shown to perturb Arabidopsis development (Yuan et al, 2014). To avoid this effect, we used the ABA INSENSITIVE 3 (ABI3) promoter, which is relatively weak and, in seeds, mostly embryo specific (Devic et al, 1996;Ng et al, 2004), to drive expression of TagRFP fusions of the four known Arabidopsis kleisin subunits, RAD21.1/SYN2, RAD21.1.2/SYN3, RAD21.3/SYN4 and Rec8/SYN1 (da Costa-Nunes et al, 2006;Dong et al, 2001). The obtained constructs were introduced into wild-type and Atscc4-1/AtSCC4 backgrounds.…”
Section: In Vivo Imaging Of Cohesin Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…Constitutive expression of cohesin subunits using 35S promoter was shown to perturb Arabidopsis development (Yuan et al, 2014). To avoid this effect, we used the ABA INSENSITIVE 3 (ABI3) promoter, which is relatively weak and, in seeds, mostly embryo specific (Devic et al, 1996;Ng et al, 2004), to drive expression of TagRFP fusions of the four known Arabidopsis kleisin subunits, RAD21.1/SYN2, RAD21.1.2/SYN3, RAD21.3/SYN4 and Rec8/SYN1 (da Costa-Nunes et al, 2006;Dong et al, 2001). The obtained constructs were introduced into wild-type and Atscc4-1/AtSCC4 backgrounds.…”
Section: In Vivo Imaging Of Cohesin Loadingmentioning
confidence: 99%
“…The Arabidopsis genome encodes four kleisin subunits (Fig. 1A): the meiosis-specific SYN1 (Cai et al, 2003) and SYN3, involved in gene expression of meiotic genes, but also expressed in somatic cells (Yuan et al, 2012;Jiang et al, 2007), and SYN2 and SYN4, which have been suggested to participate in mitotic cell division (da Costa-Nunes et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Mutants of cohesin genes, smc1 (titan8) and smc3 (titan7), show aberrant seed development in Arabidopsis (Liu et al, 2002). One of the four a-kleisin paralogs in Arabidopsis, SYN1/DETERMINATE, INFERTILE1, is necessary for sister chromatid cohesion and correct chromosome segregation during meiosis but is expressed also in meristematic tissues (Peirson et al, 1997;Bai et al, 1999;Bhatt et al, 1999;Cai et al, 2003;da Costa-Nunes et al, 2006). The other three paralogs, SYN2/RAD21.1, SYN3/RAD21.2, and SYN4/RAD21.3, are expressed in all plant tissues and may participate in sister chromatid cohesion.…”
Section: Structural Maintenance Of Chromosomes (Smc)mentioning
confidence: 99%
“…The Arabidopsis (Arabidopsis thaliana) genome contains orthologs for many of the cohesion-associated genes that have been identified in yeast, and studies have shown that the cohesion machinery is generally conserved in Arabidopsis (Bai et al, 1999;Bhatt et al, 1999;Dong et al, 2001;Chelysheva et al, 2005;Lam et al, 2005;da Costa-Nunes et al, 2006;Liu and Makaroff, 2006;Jiang et al, 2007). However, essentially nothing is known about how sister chromatid cohesion is established in plants.…”
mentioning
confidence: 99%